The Pacific Alliance: regional integration as neoliberal discipline. Issue 4 (19th May 2022) - Nelson, Marcel
ABSTRACT: This article examines how the Pacific Alliance constitutes a multilevel state project to lock-in neoliberal reforms in each member country. Using a strategic relational approach to institutions that emphasizes the interconnection between institutional and social dynamics, it demonstrates that the AP is a state project that is both a regional market access strategy and a domestic disciplinary mechanism. Notably, it represents an attempt to reinforce the neoliberal economic export models that predominate in each member country: Chile, Mexico, Peru, and Colombia. Buttressed by dominant domestic and transnational social forces in each country, technocrats in each member countries seek to reproduce institutional strategies of depoliticization that were successfully employed in their countries at a regional level in the AP in view of growing political instability and discontentment with neoliberalism.